Evaluation of knowledge about NBCAL by pharmacists and the illegal commercial promotion of breastmilk substitutes in pharmacies in a city in the countryside of Paraná (Research, Society and Development, 2023)
Objectives: to monitor the commercial promotion of breastmilk substitutes (focusing on the growing-up milk) and to assess pharmacists' knowledge about the NBCAL. Methods: cross-sectional article, conducted through direct observation in pharmacies and interviews using structured questionnaires with commercial dispensing pharmacists in the city of Toledo/PR, starting in june and ending in november 2021. Descriptive statistics were used for data analysis. Results: 58% of the pharmaceutical establishments in Toledo infringe the NBCAL, and the most common infractions are those related to the lack of mandatory wording on breast milk substitutes. The most common illegal commercial promotion strategies were: price discount, special display, sale linked to other products, prizes and giveaways. Nestle and Danone were the companies with the largest number of violations of the law. The growing-up milk was the product with the highest number of infractions related to commercial promotion. 50% of the interviewed pharmacists do not know about the NBCAL. Conclusions: it is necessary to invest in education (from graduation to professional qualification courses) to avoid the advance of infant weaning and obesity, linked to abusive marketing from industries that produce breast milk substitutes.